(untitled) (In situ, 2025)
In the autumn of 2024, small-scale archaeological trial excavations were carried out in the sub-hillfort part of the late prehistoric settlement of Kopila on the island of Korčula. Given that this is an area that was subjected to intensive agricultural cultivation in the past, the primary goal of the project was to determine the condition of the archaeological deposits in order to plan further approach to the research of this important site.